Water hyacinth (Eichhornia crassipes) for organic contaminants removal in water – A review - Farah, Amalina; Abdul Syukor, Abd Razak; Santhana, Krishnan; A. W., Zularisam; Mohd, Nasrullah (Elsevier Ltd, 2022)
Water hyacinth (WH) is well-known as an invasive species that threatens aquatic biodiversity worldwide. Manual or physical removal of this substance from water is necessary to avoid secondary water pollution caused using chemically synthesized herbicides by its control, resulting in organic waste generation. Researchers recently recommended, among other things, this waste might be converted into adsorbents that can be used for the remediation of water resources, as well as other applications. This is critically important since clean water is still required in all aspects of life, regardless of its quality. The remediation approaches presented for the treatment of water supplies through the remediation of organic contaminants utilizing WH are discussed in this study. Research into the use of WH for phytoremediation and the removal of organic contaminants has been conducted in detail. It can be seen from this review that the overview of various works was more concerned with the removal of organic dyes from water than with any other topic. A study of the underlying mechanisms in the adsorption processes is presented in this context. Towards the end of the paper, it is suggested that future research into the use of WH to remediate water resources will aid in the water resource environmental management.